1975
DOI: 10.1113/jphysiol.1975.sp010807
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic acinar cells: ionic dependence of acetylcholine‐induced membrane potential and resistance change.

Abstract: SUMMARY1. Intracellular recordings of membrane potential, input resistance and time constant have been made in vitro from the exocrine acinar cells of the mouse pancreas using glass micro-electrodes. The acinar cells were stimulated by acetylcholine (ACh). In some cases ACh was simply directly added to the tissue superfusion bath, in other experiments ACh was applied locally to pancreatic acini by micro-iontophoresis.2. Current-voltage relations were investigated by injecting rectangular de-or hyperpolarizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
65
0
1

Year Published

1977
1977
1993
1993

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 31 publications
12
65
0
1
Order By: Relevance
“…Responses with latencies less than 100 msec could not be obtained even when the pipette was only a few micrometres from the membrane. Subsequent studies have confirmed that ionophoretically applied acetylcholine or carbachol cannot evoke responses of shorter latency in smooth muscle (Bolton, 1976), frog heart (Purves, 1976) or exocrine glands (Nishiyama & Petersen, 1975).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Responses with latencies less than 100 msec could not be obtained even when the pipette was only a few micrometres from the membrane. Subsequent studies have confirmed that ionophoretically applied acetylcholine or carbachol cannot evoke responses of shorter latency in smooth muscle (Bolton, 1976), frog heart (Purves, 1976) or exocrine glands (Nishiyama & Petersen, 1975).…”
Section: Introductionmentioning
confidence: 91%
“…This is true for nerve-mediated responses not only in heart, as indicated above, but also in smooth muscle, salivary glands, pancreas, sympathetic ganglia and spinal cord Renshaw cells. Responses to ionophoretically applied acetylcholine or carbachol are also slow (Purves, 1976;Bolton, 1976;Nishiyama & Petersen, 1975) even when application is made at very short distances from the cell membrane and monitored with high-resolution optics (Purves, 1974;Hartzell, Kuffler, Stickgold & Yoshikami, 1977 Adrenergic responses The responses of heart muscle cells to catecholamines showed kinetic peculiarities qualitatively similar to those of responses to muscarinic agonists, but to a much greater extent. Reuter (1974) applied noradrenaline ionophoretically to Purkinje fibres of sheep and calves and obtained increases in the rate of spontaneous beating when he ejected charges of several /tC outside the cells.…”
mentioning
confidence: 99%
“…It has recently been established that one of the earliest steps occurring at the acinar cell membrane in response to stimulation by ACh and pancreozymin is an increase in the permeability to Na+ with a consequent depolarization (Matthews & Petersen, 1973;Nishiyama & Petersen, 1974;Nishiyama & Petersen, 1975 (Pressman, 1973;Case, Vanderkooi & Scarpa, 1974). Also the failure of A23187 to evoke any marked depolarization at a Mg2+ concentration of 10 mm in the absence of Ca2+ makes the simple interpretation unlikely, since it is known that the ionophore complexes Mg2+ equally well as Ca2+ (Reed & Lardy, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that a tenfold reduction in the extracellular concentration resulted in a 15 mV positive shift of the null-potential. INTRODUCTION In previous studies on the ionic dependency of the acetylcholine-evoked depolarization of pancreatic acinar cells, it was suspected (Nishiyama & Petersen, 1975) and later confirmed (Iwatsuki & Petersen, 1977b) that, in addition to Na+ and K+, the permeability of the acinar cell membrane to Cl-also increased after ACh stimulation.…”
mentioning
confidence: 99%